The Infancy Canticles in Luke - Matteo Crimella (Wrocławski Przegląd Teologiczny)
The article focuses on the four canticles in Luke’s Infancy Narrative (Magnificat, Benedictus, Gloria and Nunc dimittis) and puts a question about why there is a passage from prose to poetry. The studies of the so-called inset psalms and the research on the Psalter as a book led to a backward and a forward approach. The former is that of intertextuality, showing how Luke’s canticles evoke texts of the Old Testament. Alluding to Scripture, whose status as inspired and canonical text is a truth that concerns the protagonists, the evangelist and also the recipients of the work, the narrator invites the reader to accept that hymn as the Word of God for today. The latter highlights “melodic lines” introduced by the canticles in the works of Luke (Gospel and Acts). The four canticles are closely concatenated so as to become privileged hermeneutical places for understanding the sense of the whole narrative. Why, then, does Luke introduce his canticles? They underline their strongly anthropological value and represent a response to the salvific event. This response participates in the event itself because only through it is communicated the fullness of what the Lord has performed, is performing and will perform in the future.